Development of Risk Maps and Implementation of Socialization of Earthquake Disaster Mitigation in Matano Village, East Luwu Regency - Pramatadie, Andi Muhamad; Drajat, Elzaskiah; Sari , Nurmala (International Journal for Disaster and Development Interface, 2025)
Community service activities in Matano Village, East Luwu Regency, with a focus on developing earthquake risk maps and disaster mitigation pocketbooks, were carried out from July 8 to August 15, 2024. Given the geographical location of Matano Village adjacent to the Matano Fault, which has a high potential risk of earthquakes, this activity aims to increase community preparedness in dealing with disasters. Through the Real Work Lecture (KKN) conducted by Hasanuddin University, data was downloaded from InaRisk BNPB, followed by socialization to the public about earthquake risk and mitigation measures that need to be taken. The results of this activity are in the form of risk maps and pocket books which are expected to increase public understanding and awareness of potential earthquake disasters. This research is expected to be a reference in disaster mitigation efforts, especially in earthquake-prone areas.